2228. Late Viral Relapse After Direct-Acting Antiviral Treatment in Hepatitis C Virus-Infected Cancer Patients. (26th November 2018) - Angelidakis, Georgios; Nowbakht, Cima; Torres, Harrys
Abstract: Background: According to professional societies, the endpoint to consider hepatitis c virus (HCV) infection cured is the achievement of a sustained virologic response 12 weeks after treatment completion (SVR12). Late recurrences (beyond SVR12) are rare. Herein, we report two cases of HCV-infected cancer patients with late relapses post direct-acting antivirals (DAAs). Methods: Patients with any type of chronic cancer and HCV treated with DAAs between January 2014 and March 2018 at MD Anderson Cancer Center were prospectively followed. All patients had HCV RNA levels at baseline; 2 and 4 weeks after initiation of DAAs; at end of treatment (EOT); and 12 weeks after completion of DAAs. No phylogenetic analyses were available for samples collected. Results: Among 196 HCV-infected cancer patients treated with DAAs, 20 developed viral relapse, 2 (10%) of them with late relapse (Figure 1). Both patients denied behaviors, exposures, and conditions associated with HCV reinfection. Case 1 : Fifty-six-year-old male with hepatocellular carcinoma (HCC), HCV genotype 1a, interferon-experienced, with compensated cirrhosis received in 2017 ledipasvir/sofosbuvir for 12 weeks, followed by systemic chemotherapy with sorafenib. He achieved an SVR12 but developed HCV relapse 12 weeks later (24 weeks after EOT). Patient remained infected with HCV 1a. He did not receive retreatment due to HCC not amenable for curative treatment. Case 2 : 57-year-old male with multiple myeloma, HCV genotype 1a, interferon-experienced without cirrhosis. He received sofosbuvir and simeprevir in 2015 for 12 weeks. Post DAAs, he received chemotherapy with carfilzomib, lenalidomide, dexamethasone, and ixazomib followed by autologous hematopoietic cell transplant pre-conditioned with melphalan. He achieved both an SVR12 and SVR 24 but had HCV relapse detected during the one year follow-up visit. Patient remained infected with HCV 1a. He has retreated with sofosbuvir, veltapasvir, voxilaprevir and ribavirin and currently with HCV RNA level at EOT. Conclusion: Late HCV relapses can occur in HCV-infected cancer patients. Long-term monitoring of HCV-RNA and easy-to-use tests to differentiate relapses from reinfection in real-world practice are warranted in this population. Disclosures: H. Torres, Gilead Sciences, Merck & Co., Inc.: Grant Investigator, Grant recipient. Vertex Pharmaceuticals: Grant Investigator, Grant recipient.